Macroprudential supervision of financial institutions: Lessons from the SCAP - Beverly Hirtle; Til Schuermann; Kevin Stiroh (Federal Reserve Bank of New York, 2009)
A fundamental conclusion drawn from the recent financial crisis is that the supervision and regulation of financial firms in isolation - a purely microprudential perspective - are not sufficient to maintain financial stability. Rather, a macroprudential perspective, which evaluates and responds to the financial system as a whole, seems necessary, and the ongoing discussions of regulatory reform in the United States underscore this view. The recently concluded Supervisory Capital Assessment Program (SCAP), better known as the bank 'stress test,' is one example of how the macro- and microprudential perspectives can be joined to create a stronger supervisory framework that addresses a wider range of supervisory objectives. This paper reviews the key features of the SCAP and discusses how they can be leveraged to improve bank supervision in the future.
Keywords: G21; G28; G20; 330; Bank stress test; macroprudential; SCAP; bank supervision; Bankenaufsicht; USA